Multiplication of Environmental Labelling and Information Schemes (ELIS) Implications for Environment and Trade - Prag, Andrew (OECD Publishing, 2016)
This report explores potential effects of the recent rapid growth in Environmental Labelling Information Schemes (ELIS) around the world, with a focus on the implications of ELIS multiplication for environmental effectiveness and international trade. As empirical work on the environmental effects of ELIS multiplication is just beginning to appear, insights from the theoretical literature on label competition are presented. Modelling suggests that competition between labels may reduce environmental performance relative to a single label with strict environmental goals, though stylised modelling may not accurately reflect the complex real-world interactions of schemes. The analysis is complemented with an overview of empirical studies on environmental effects, including evidence that label competition has led to market-driven convergence of standards in some sectors, such as forest certification.
Keywords: Environment